THE PRINCIPLE OF PROPORTIONALITY IN FRANCHISE AGREEMENTS: IMPLICATIONS AND PRACTICES IN BUSINESS CONTRACTUAL RELATIONSHIPS - Mia Rasmiaty (JILPR Journal Indonesia Law and Policy Review, 2025)
The principle of proportionality plays a very important role in maintaining the balance between the rights and obligations of the parties to a franchise agreement. In practice, franchise agreements often exhibit an imbalance between the franchisor and franchisee, potentially to the detriment of the weaker party. This article discusses the implications of the principle of proportionality in franchise agreements in Indonesia, focusing on how its application can prevent contractual imbalance. It also explores the best practices and regulations needed to ensure a fairer and more proportional application of this principle in franchise agreements. The research method used is a normative juridical method that relies on the analysis of the relevant legal framework, especially related to the regulation of franchise agreements in Indonesia. The results of the discussion show that strengthening regulations, dispute resolution mechanisms, and the application of transparency and balance principles in agreements can create a fairer and more sustainable business climate.